Improving fluorescence imaging of biological cells on biomedical polymers - Jaafar, Israd Hakim; LeBlon, Courtney E.; Wei, Ming-Tzo; Ou-Yang, Daniel; Coulter, John P.; Jedlicka, Sabrina S. (Elsevier, 2011)
Immunoﬂuorescence imaging on polymeric biomaterials is often inhibited by autoﬂuorescence and other optical phenomena. This often limits the analysis that can be performed on cells that are in contact with these materials. This study outlines a method that will quench these inhibitive optical phenomena on a variety of polymeric materials, including poly(glycerol sebacate), poly(urethane), poly(L-lactide–co-ecaprolactone), and poly(lactic acid–co-glycolic acid). The method uses a simple material treatment method utilizing Sudan Black B (SB), which is commonly used as an autoﬂuorescence quenching molecule in tissue histology, but has not yet been used in biomaterials analysis. The quenching mechanism in the selected polymers is investigated using attenuated total reﬂectance Fourier transform infrared spectroscoy, ultraviolet–visible light absorbance and ﬂuorescence analysis, and scanning electron microscopyobservation of the material morphology prior to and after SB treatment. The results point to SB eliminating the inhibitive light phenomena of these materials by two methods: (i) chemical interaction between SB and the polymer molecules and (ii) physical interaction whereby SB forms a physical barrier that can absorb scattered light and quench autoﬂuorescence interference during ﬂuorescence microscopy. The studies show that the treatment of polymers with SB is robust across the polymers tested, in both porous and non-porous formats. The method does not interfere with immunoﬂuorescent imaging of ﬂuorescently labeled biological cells cultured on these polymers. This quick, simple, and affordable method enables a variety of analyses to be conducted that may otherwise have been impractical or impossible.